Community Behavior in the Use of Coral Rocks for Development in Karas Village - Handre Kurnia S.; Nanik Rahmawati; Rahma Syafitri (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
Coral is a natural resource widely used by people living in coastal areas. Most of the community behavior in the use of coral reefs is used for the foundation of the house as a building material for a house. This study aims to describe people's behavior in using coral reefs as building materials. This research method is qualitative with in-depth interview, observational and documentary data collection techniques. The technique of data analysis in this study is by data reduction, data presentation and drawing conclusions. Research results show that. Behavior based on the community's unwillingness to provide commonly used building materials. Anthropocentrism's view of the environment considers people as the center of nature, nature is only seen as a tool to meet human needs. This is the reason why people exploit coral reefs, reducing fishermen's income and destroying the environment. In addition, proximity and availability of natural resources also affect how people use resources. So people tend to utilize existing resources in their neighborhood to meet their needs.